Preparation method of fluorinated polymer solid-state in-situ high-voltage battery
By using fluorine-containing polycarbonate-based solid electrolyte materials and in-situ assembly process in lithium metal batteries, the problem of poor stability and film formation performance of electrolytes at high voltage is solved, and a high energy density and long-life battery is achieved performance.
Patent Information
- Application Number
- CN202111067175.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-14
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-09-14
AI Technical Summary
The solid electrolytes of existing lithium metal batteries have poor electrochemical stability at high voltages, low conductivity, and poor film-forming performance of polyester electrolytes, making it difficult to meet the needs of high energy density and long life.
Fluorine-containing polycarbonate-based solid electrolyte material is used to expand the electrochemical window by introducing fluorine elements, and combined with in-situ assembly process, the battery interface impedance is reduced and the conductivity is improved.
It significantly improves the oxidation potential of the electrolyte, broadens the electrochemical window, reduces the battery interface impedance, achieves high energy density and good battery performance, and is suitable for high-voltage lithium metal batteries.
Smart Images

Figure CN115810802B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium metal polymer solid-state batteries, and in particular, relates to a method for preparing a fluorine-containing polycarbonate copolymer solid-state electrolyte material for use as a high-voltage lithium metal battery electrolyte material and an in-situ assembly technology for the battery. Background Art
[0002] As an energy storage material, lithium-ion batteries have been widely used in various electronic devices in our lives. However, with the rapid development of electric vehicles, portable devices, and various flexible wearable devices, the demand for battery energy with lighter weight, smaller size, higher output voltage and energy density continues to expand. The energy density of commercial lithium-ion batteries with graphite as negative electrode (372mAh g -1 ) cannot fully meet the emerging market demand; while the development of lithium metal batteries, which was once hindered by the limitations of liquid electrolytes, has turned around with the breakthrough of solid polymer electrolytes. Lithium metal as a negative electrode has a very high theoretical specific capacity (3860mAh g -1 ), the lowest electrochemical potential (-3.04 V) and the lowest density (0.53 g cm -3 ), therefore, high-voltage lithium metal batteries with high energy density positive electrode materials (such as lithium-manganese-rich, lithium nickel manganese oxide, ternary positive electrodes, etc.) have extremely high theoretical energy density and are ideal power devices for current electronic devices.
[0003] Polyether solid electrolytes, headed by polyethylene oxide, are the most studied polymer solid electrolytes and are widely used in lithium-ion batteries. However, there are certain problems with the application of polyether polymer electrolytes in high-voltage lithium metal batteries: first, the electrochemical stability of the electrolyte is poor. The electrochemical window of polyethylene oxide electrolyte is only about 4.0V, while the voltage platform of high-energy-density battery systems is often higher than 4.5V and has a wide operating voltage range, which makes polyether electrolytes easily oxidized and decomposed under high voltages. The capacity of the battery will decay rapidly during the battery cycle. On the other hand, polyether electrolytes are highly crystalline polymers, and the Li+ conductivity at room temperature is less than 10 -6 S / cm, which makes the solid-state lithium metal battery based on polyethylene oxide play its own advantages. Although many studies have made a series of improvements to the polyethylene oxide electrolyte system, such as improving mechanical properties and reducing crystallinity by blending nanofillers, and improving its electrochemical window by copolymerization, etc., although the performance of the electrolyte will be improved to a certain extent, it is still difficult to meet the requirements of working under high voltage.
[0004] Compared with polyether solid electrolytes, polycarbonate electrolytes have a wider electrochemical window, which is due to the lower HOMO energy level of the carbonyl group in the carbonate than the ether bond, and stronger oxidation resistance; in addition, due to its amorphous structure, it has a higher room temperature ionic conductivity than polyether electrolytes, so polycarbonate electrolytes are more suitable for high-voltage lithium metal batteries. Cyclic carbonates such as ethylene carbonate and vinyl ethylene carbonate have a high dielectric constant, which makes them more conducive to the dissolution and ionization of lithium salts, making them more conducive to their application in solid electrolytes. However, the electrochemical window of these polycarbonate solid electrolytes is generally around 4.4V, which is still not enough for use in high-voltage lithium metal batteries. In addition, these molecules can only obtain low molecular weight due to the self-inhibition effect, resulting in poor processing performance and difficulty in obtaining electrolyte films, thus limiting their application. Recently, with the maturity of in-situ polymerization technology, these electrolytes have been further developed, but the current in-situ polymerization process requires cellulose diaphragms as support, which increases the cost and process complexity of battery preparation.
[0005] Fluorine is the element with the strongest electronegativity. In electrochemical reactions, fluorine atoms can greatly increase the oxidation potential of compounds. Therefore, the development of fluorine-containing polyester-based electrolytes can enable polymer electrolytes to have a higher voltage platform, which is of great significance for high-voltage lithium batteries. Summary of the invention
[0006] In view of the problems in the prior art such as low electrochemical window of polymer solid electrolytes, difficulty in molding of polyester electrolytes, poor film-forming performance, and excessively high interface impedance of solid-state batteries, a method for preparing a series of fluorine-containing polycarbonate-based solid electrolyte materials for lithium metal battery electrolyte materials is provided, wherein the introduction of fluorine element can significantly increase the oxidation potential of the electrolyte and thus broaden the electrochemical window, and the in-situ battery assembly process greatly reduces the battery interface impedance so that the battery can operate at room temperature.
[0007] A method for preparing a fluorinated polymer solid-state in-situ high-voltage battery comprises the following steps:
[0008] 1) In a glove box, unsaturated fluorine-containing monomer, unsaturated carbonate monomer, thermal initiator and cross-linking agent are mixed and added into a reagent bottle, and stirred at a speed of 50-100 r / min for 20-40 min to be fully mixed, which is recorded as prepolymer solution A. The unsaturated fluorine-containing monomer in the prepolymer solution is a fluorine-containing compound containing a double bond, which can be trifluoroethyl methacrylate; the unsaturated carbonate monomer is a carbonate compound containing a double bond, which can be vinyl ethylene carbonate; the thermal initiator is a compound that can be dissolved in the monomer and can initiate free radical polymerization within a specified temperature, which can be azobisisobutyronitrile; the cross-linking agent is a compound that has multiple double bonds and is miscible with the monomer, which can be butanediol diacrylate;
[0009] 2) heating the prepolymer solution A obtained in step 1) at 40-80° C. for 1-5 h on an electronic thermostatic heating plate, and then adding LiTFSI, which is recorded as prepolymer solution B, wherein the amount of LiTFSI is 30%-50% of the mass fraction of the prepolymer solution;
[0010] 3) mixing a high-voltage positive electrode material, polyvinylidene fluoride, and conductive carbon black in a glove box at a ratio of 8:1:1 and grinding them in an agate mortar for 30-120 minutes, adding a small amount of N-methylpyrrolidone to mix into a uniform coating, then transferring it to a carbon-coated aluminum foil and using a coater to scrape it into a 50-300 μm thick coating, transferring it to a heating table and drying the solvent at a temperature of 80-120° C. for 8-12 hours to obtain a high-voltage positive electrode coating, wherein the high-voltage positive electrode material can be NCM811 and a lithium-rich manganese-based layered transition metal oxide;
[0011] 4) The prepolymer solution B described in step 2) is evenly applied on one side of the polished lithium metal sheet, heated on an electronic constant temperature heating plate at 60-80° C. for 8-16 hours, and then the negative electrode shell, spring gasket, stainless steel gasket, lithium sheet, prepolymer electrolytic solution, positive electrode coating described in step 3) and positive electrode shell are assembled from bottom to top, which is recorded as an in-situ battery pack;
[0012] 5) placing the in-situ battery pack described in step 4) on a constant temperature heating plate at 70-80° C. for 10-30 hours to complete the polymerization of the monomers, and packaging the battery pack after the reaction is complete to obtain a high-voltage in-situ solid-state battery;
[0013] 6) Test high voltage in-situ solid-state battery performance.
[0014] The specific instructions are as follows:
[0015] The polymer main body of the fluorine-containing polymer solid-state in-situ high-voltage battery of the present invention is mainly a fluorine-containing polymer solid electrolyte. Different from the traditional polymer solid electrolyte, the fluorine atoms greatly increase the oxidation potential of the polymer, thereby greatly broadening the electrochemical window of the polymer electrolyte. The in-situ high-voltage battery assembled by combining the in-situ polymerization process has the characteristics of small interface impedance and high electrical conductivity.
[0016] Beneficial effects of the present invention:
[0017] The raw materials of the present invention are simple, readily available and cheap. Through a simple in-situ polymerization process, an electrolyte can be formed in situ on the surface of lithium metal. The operation is simple and easy for large-scale production and mechanized operation. The fluorine-containing polycarbonate electrolyte has the characteristics of high electrochemical window and high ionic conductivity. The assembled in-situ high-voltage battery has a high charge and discharge platform, a high energy density and excellent battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Schematic diagram of the polymerization reaction of fluorinated copolymer poly(ethylene carbonate)-trifluoroethyl methacrylate;
[0019] Figure 2 is the infrared spectrum of poly(ethylene carbonate)-trifluoroethyl methacrylate;
[0020] Figure 3 is the H NMR spectrum of poly(vinylethylene carbonate)-trifluoroethyl methacrylate;
[0021] Figure 4 is the ionic conductivity-temperature diagram of the polymer poly(ethylene carbonate)-trifluoroethyl methacrylate-LiTFSI electrolyte;
[0022] Figure 5 It is the electrochemical window of the polymer poly(ethylene carbonate)-trifluoroethyl methacrylate-LiTFSI electrolyte;
[0023] Figure 6 This is the interface impedance diagram of the high-voltage solid-state battery;
[0024] Figure 7 This is the cycle performance diagram of NCM811 high-voltage solid-state battery;
[0025] Figure 8 This is the charge and discharge energy diagram of NCM811 high voltage solid-state battery;
[0026] Fig. 9 This is a graph showing the cycling performance of lithium-rich manganese-based layered transition metal oxide high-voltage solid-state batteries;
[0027] Fig.10 This is a graph showing the cycling performance of a lithium-manganese-rich layered transition metal oxide high-voltage solid-state battery. DETAILED DESCRIPTION
[0028] Drug purchase source:
[0029] Ethylene carbonate and trifluoroethyl methacrylate were analytically pure reagents purchased from Sane Chemical Technology (Shanghai) Co., Ltd.; butanediol diacrylate and azobisisobutyronitrile were chemically pure reagents purchased from Shanghai MacLean Reagent Co., Ltd.; N-methylpyrrolidone, polyvinylidene fluoride, conductive carbon black, NCM811 and lithium-rich manganese-based layered transition metal oxides were purchased from Shenzhen Kejing Company.
[0030] Battery performance test: The battery was connected to the LAND battery test system and left to stand for 24 hours before constant current charge and discharge performance test was performed. The discharge current density was 27.5 mA g -1 The test voltage range is 3V-4.8V, and the test uses button batteries to directly measure the data.
[0031] Example 1
[0032] 1) In a glove box, 0.2 mL of trifluoroethyl methacrylate, 1.02 mL of vinyl ethylene carbonate monomer, 20 mg of azobisisobutyronitrile and 0.02 mL of butanediol diacrylate were mixed and added into a reagent bottle, and stirred at a speed of 50 r / min for 40 min to fully mix, which was recorded as prepolymer solution A;
[0033] 2) heating the prepolymer solution A obtained in step 1) at 40° C. for 5 h on an electronic thermostatic heating plate, and then adding 30% LiTFSI, which is recorded as prepolymer solution B;
[0034] 3) 160 mg of NCM811, 20 mg of polyvinylidene fluoride, and 20 mg of conductive carbon black were mixed in a glove box and ground with an agate mortar for 120 min, and a small amount of N-methylpyrrolidone was added to mix into a uniform coating, which was then transferred to a carbon-coated aluminum foil and coated with a coater to form a 300 μm thick coating, and then transferred to a heating table and dried at 120° C. for 12 h to obtain a high-voltage positive electrode coating;
[0035] 4) The prepolymer solution B described in step 2) is evenly applied on one side of the polished lithium metal sheet, heated on an electronic constant temperature heating plate at 80° C. for 16 hours, and then assembled in the order of negative electrode shell, spring gasket, stainless steel gasket, lithium sheet, prepolymer electrolytic solution, positive electrode coating described in step 3) and positive electrode shell from bottom to top, which is recorded as an in-situ battery pack;
[0036] 5) placing the in-situ battery pack described in step 3) on a constant temperature heating plate at 80° C. for 30 hours to complete the polymerization of the monomers, and packaging the battery pack after the reaction to obtain a high-voltage in-situ solid-state battery;
[0037] 6) The test shows that the initial specific capacity of the high-voltage in-situ solid-state battery is 220 mAh / g.
[0038] Example 2
[0039] 1) In a glove box, 0.2 mL of trifluoroethyl methacrylate, 1.02 mL of vinyl ethylene carbonate monomer, 20 mg of azobisisobutyronitrile and 0.02 mL of butanediol diacrylate were mixed and added into a reagent bottle, and stirred at a speed of 100 r / min for 40 min to mix thoroughly, which was recorded as prepolymer solution A;
[0040] 2) heating the prepolymer solution A obtained in step 1) at 80° C. for 1 h on an electronic thermostatic heating plate, and then adding 50% LiTFSI, which is recorded as prepolymer solution B;
[0041] 3) 160 mg of lithium-rich manganese-based layered transition metal oxide, 20 mg of polyvinylidene fluoride, and 20 mg of conductive carbon black were mixed in a glove box and ground using an agate mortar for 30 min, and a small amount of N-methylpyrrolidone was added to mix into a uniform coating, which was then transferred to a carbon-coated aluminum foil and coated with a coater to form a 50 μm thick coating, and then transferred to a heating table and dried at a temperature of 120° C. for 12 h to obtain a high-voltage positive electrode coating;
[0042] 4) The prepolymer solution B described in step 2) is evenly applied on one side of the polished lithium metal sheet, heated at 60° C. for 8 h on an electronic constant temperature heating plate, and then assembled in the order of negative electrode shell, spring gasket, stainless steel gasket, lithium sheet, prepolymer electrolytic solution, positive electrode coating described in step 3) and positive electrode shell from bottom to top, which is recorded as an in-situ battery pack;
[0043] 5) placing the in-situ battery pack described in step 3) on a constant temperature heating plate at 70° C. for 10 hours to complete the polymerization of the monomers, and packaging the battery pack after the reaction is complete to obtain a high-voltage in-situ solid-state battery;
[0044] 6) The test shows that the initial specific capacity of the high-voltage in-situ solid-state battery is 280 mAh / g.
[0045] Example 3
[0046] 1) In a glove box, 0.2 mL of trifluoroethyl methacrylate, 1.02 mL of vinyl ethylene carbonate monomer, 20 mg of azobisisobutyronitrile and 0.02 mL of butanediol diacrylate were mixed and added into a reagent bottle, and stirred at a speed of 50 r / min for 40 min to fully mix, which was recorded as prepolymer solution A;
[0047] 2) heating the prepolymer solution A obtained in step 1) at 40° C. for 5 h on an electronic thermostatic heating plate, and then adding 40% LiTFSI, which is recorded as prepolymer solution B;
[0048] 3) 160 mg of NCM811, 20 mg of polyvinylidene fluoride, and 20 mg of conductive carbon black were mixed in a glove box and ground with an agate mortar for 120 min, and a small amount of N-methylpyrrolidone was added to mix into a uniform coating, which was then transferred to a carbon-coated aluminum foil and coated with a coater to form a 300 μm thick coating, and then transferred to a heating table and dried at 120° C. for 12 h to obtain a high-voltage positive electrode coating;
[0049] 4) The prepolymer solution B described in step 2) is evenly applied on one side of the polished lithium metal sheet, heated on an electronic constant temperature heating plate at 80° C. for 16 hours, and then assembled in the order of negative electrode shell, spring gasket, stainless steel gasket, lithium sheet, prepolymer electrolytic solution, positive electrode coating described in step 3) and positive electrode shell from bottom to top, which is recorded as an in-situ battery pack;
[0050] 5) placing the in-situ battery pack described in step 3) on a constant temperature heating plate at 80° C. for 30 hours to complete the polymerization of the monomers, and packaging the battery pack after the reaction to obtain a high-voltage in-situ solid-state battery;
[0051] 6) The test shows that the initial specific capacity of the high-voltage in-situ solid-state battery is 218 mAh / g.
[0052] Example 4
[0053] 1) In a glove box, 0.2 mL of trifluoroethyl methacrylate, 1.02 mL of vinyl ethylene carbonate monomer, 20 mg of azobisisobutyronitrile and 0.02 mL of butanediol diacrylate were mixed and added into a reagent bottle, and stirred at a speed of 50 r / min for 40 min to fully mix, which was recorded as prepolymer solution A;
[0054] 2) heating the prepolymer solution A obtained in step 1) at 40° C. for 5 h on an electronic thermostatic heating plate, and then adding 50% LiTFSI, which is recorded as prepolymer solution B;
[0055] 3) 160 mg of NCM811, 20 mg of polyvinylidene fluoride, and 20 mg of conductive carbon black were mixed in a glove box and ground with an agate mortar for 120 min, and a small amount of N-methylpyrrolidone was added to mix into a uniform coating, which was then transferred to a carbon-coated aluminum foil and coated with a coater to form a 300 μm thick coating, and then transferred to a heating table and dried at 120° C. for 12 h to obtain a high-voltage positive electrode coating;
[0056] 4) The prepolymer solution B described in step 2) is evenly applied on one side of the polished lithium metal sheet, heated on an electronic constant temperature heating plate at 80° C. for 16 hours, and then assembled in the order of negative electrode shell, spring gasket, stainless steel gasket, lithium sheet, prepolymer electrolytic solution, positive electrode coating described in step 3) and positive electrode shell from bottom to top, which is recorded as an in-situ battery pack;
[0057] 5) placing the in-situ battery pack described in step 4) on a constant temperature heating plate at 80° C. for 30 hours to complete the polymerization of the monomers, and packaging the battery pack after the reaction is complete to obtain a high-voltage in-situ solid-state battery;
[0058] 6) The initial specific capacity of the high-voltage in-situ solid-state battery was found to be 210 mAh / g
[0059] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A method for preparing a fluorinated polymer solid-state in-situ high-voltage battery, characterized in that: The following steps are involved: 1) In a glove box, unsaturated fluorine-containing monomer, unsaturated carbonate monomer, thermal initiator and crosslinking agent are mixed and added into a reagent bottle, and stirred at a speed of 50-100 r / min for 20-40 min to be fully mixed, which is recorded as prepolymer solution A. The unsaturated fluorine-containing monomer in the prepolymer solution A is trifluoroethyl methacrylate, a fluorine-containing compound containing a double bond; the unsaturated carbonate monomer is a carbonate compound containing a double bond; 2) heating the prepolymer solution A obtained in step 1) at 40-80° C. for 1-5 h on an electronic constant temperature heating plate, and then adding LiTFSI, which is recorded as prepolymer solution B; 3) The high-voltage positive electrode material, polyvinylidene fluoride, and conductive carbon black are mixed in a glove box at a ratio of 8:1:1 and ground using an agate mortar for 30-120 minutes, a small amount of N-methylpyrrolidone is added to mix into a uniform coating, which is then transferred to a carbon-coated aluminum foil and coated with a coating applicator to form a 50-300 μm thick coating, which is then transferred to a heating table and dried at a temperature of 80-120° C. for 8-12 hours to obtain a high-voltage positive electrode coating; 4) The prepolymer solution B described in step 2) is evenly coated on one side of the polished lithium metal sheet and heated by an electronic constant temperature. The plate is heated at 60-80° C. for 8-16 hours, and then the negative electrode shell, spring gasket, stainless steel gasket, lithium sheet, prepolymer electrolytic solution, positive electrode coating described in step 3) and positive electrode shell are assembled from bottom to top, which is recorded as an in-situ battery pack; 5) placing the in-situ battery pack described in step 4) on a constant temperature heating plate at 70-80° C. for 10-30 hours to complete the polymerization of the monomers, and packaging the battery pack after the reaction is complete to obtain a high-voltage in-situ solid-state battery; Among them, the carbonate compound containing double bonds is vinyl ethylene carbonate; the cross-linking agent is butanediol diacrylate; and the high-voltage positive electrode material is NCM811 and a lithium-rich manganese-based layered transition metal oxide.
2. The preparation method according to claim 1, characterized in that: The thermal initiator is azobisisobutyronitrile, a compound that is dissolved in the monomer and initiates free radical polymerization within a specified temperature.